(untitled) (Research, Society and Development, 2023)
The importance of mapping the literature on research on the emotions of Brazilian elderly people makes it possible to know the peculiarities of emotional processes, their vision and challenges to be faced in this area. Objective: To map and categorize the main concepts found in the scientific/academic environment that support the treatment of the emotions of the elderly. Methodology: The JBI methodology was used for scoping reviews, with research in the following databases: BVS, Portal Periódicos Capes, PsycInfo, Pubmed/NIH, Scopus and Web of Science, with the descriptors Elderly, Emotions and Brazil, in Portuguese, English and Spanish. Results: 838 articles were found in the database search and 1 article in the references, 11 studies were selected, 7 of which dealt with the theme of health and well-being, 2 on social issues of emotions (cognition and constructionism), 1 on positive psychology and 1 on the construction of an instrument to assess emotions. The emotions that most emerged were the universal emotions, with emphasis on fear and sadness. Final considerations: When it comes to emotions in the elderly, research has sought to assess the negative aspects of emotions and their interference in the health and well-being of the elderly, generally carrying out studies with a cross-sectional design, with fear and sadness as the main emotions, as evidenced in the objectives and research questions of the articles in this sample. The main contexts of study are in health and in the social area.